2022
DOI: 10.3389/fgene.2022.877646
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Nanopore and Illumina Sequencing Reveals Alternative Splicing Complexity in Pig Longissimus Dorsi Muscle

Abstract: Alternative splicing (AS) is a key step in the post-transcriptional regulation of gene expression that can affect intramuscular fat (IMF). In this study, longissimus dorsi muscles from 30 pigs in high- and low- IMF groups were used to perform Oxford Nanopore Technologies (ONT) full-length sequencing and Illumina strand-specific RNA-seq. A total of 43,688 full-length transcripts were identified, with 4,322 novel genes and 30,795 novel transcripts. Using AStalavista, a total of 14,728 AS events were detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Not all clean reads were assigned to that feature, and this is probably because the pig genome was not completely annotated, so a part of the remaining reads was not assigned. However, through these reads, it would be possible to update the annotation of the pig genome [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Not all clean reads were assigned to that feature, and this is probably because the pig genome was not completely annotated, so a part of the remaining reads was not assigned. However, through these reads, it would be possible to update the annotation of the pig genome [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to the presence of some muscle-specific splicing factors in muscle tissue [49][50][51]. Previous studies have also indicated significant differences in AS events between lean and obese-type pigs in skeletal muscle [52]. Specifically, there were numerous AS events related to mitochondrial function and glucose metabolism in the skeletal muscle of lean-type pigs.…”
Section: Discussionmentioning
confidence: 96%
“…The accuracies of transcript assembly and expression quantification have been further improved due to the later single-molecule long-read RNA sequencing technologies ( 40 ). Therefore, long-read sequencing technologies are expecting to be increasingly used in transcriptome studies ( 41 ), such as in cattle ( 42 ), pigs ( 43 ), and chicken ( 44 ). In rabbit, Chen et al ( 24 ) first used PacBio long-read sequencing technology for exploring transcriptomic landscape and revealed a large proportion of novel genes and transcripts using a pooling sample of multiple organ tissues sampled at different ages.…”
Section: Discussionmentioning
confidence: 99%